Surgically Treated Hernia following Abdominally Based Autologous Breast Reconstruction: Prevalence, Outcomes, and Expenditures. Issue 3 (March 2016) - Shubinets, Valeriy; Fox, Justin P.; Sarik, Jonathan R.; Kovach, Stephen J.; Fischer, John P.
Abstract : Background: Donor-site hernia is one of the most feared complications following abdominally based autologous breast reconstruction. The authors aim to assess the incidence of surgically repaired abdominal hernia across different types of abdominally based breast reconstruction, identify predictive perioperative factors, and estimate the health care charges associated with this morbidity. Methods: Using inpatient and ambulatory surgery data from four states in the United States, the authors identified adult women who underwent pedicled transverse rectus abdominis muscle (TRAM), free TRAM, or deep inferior epigastric perforator (DIEP) flap breast reconstruction between 2008 and 2012. The primary outcome was surgical repair of abdominal hernia within 4 years. Multivariate Cox proportional hazards regression modeling was used to compare outcomes between groups. Results: The final sample included 8246 women who underwent pedicled TRAM (29.2 percent), free TRAM (30.0 percent), or DIEP (40.8 percent) flap reconstruction. The frequency of surgically repaired abdominal hernia following breast reconstruction was highest among the pedicled TRAM flap group (pedicled TRAM, 7.0 percent; free TRAM, 5.7 percent; DIEP, 1.8 percent). A hospital encounter for hernia repair, whether inpatient or ambulatory, generated substantial health care charges (pedicled TRAM, $39, 704; free TRAM, $48, 378; DIEP, $46, 481). On multivariate analysis, patients who developed a surgical-site infection within 30 days of discharge (incidence rate ratio, 1.99; 95 percent CI, 1.44 to 2.75) had a higher incidence of surgically repaired abdominal hernia. Conclusions: Surgically repaired abdominal hernia is common following abdominally based autologous breast reconstruction and is associated with significant health care expenditures. The authors demonstrate that the amount of rectus muscle sacrificed correlates to the likelihood of developing a surgically repaired abdominal hernia, and identify surgical-site infection as a predictive perioperative factor. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.